2021
DOI: 10.2196/27379
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Digital Tools Into Community Mental Health Care Settings That Serve Young People: Focus Group Study

Abstract: Background: Digital mental health tools have substantial potential to be easily integrated into people's lives and fundamentally impact public health. Such tools can extend the reach and maximize the impact of mental health interventions. Before implementing digital tools in new settings, it is critical to understand what is important to organizations and individuals who will implement and use these tools. Given that young people are highly familiar with technology and many mental health concerns emerge in chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“… What are the determinants that may affect implementation of the DMHI and strategies that address those determinants? Community Engagement/Relationship Building ( Hayes, 2014 ; Le Dantec and Fox, 2015 ; Stiles-Shields et al, 2022 ) Volunteering Community meetings ( Harrington et al, 2019 ; Lu et al, 2023 ) Needs Elicitation Focus Groups ( Knapp et al, 2021 ; Kruzan et al, 2022a ; Lattie et al, 2020b ; Makosky Daley et al, 2010 ; Powell et al, 1996 ) Co-Design Workshops Interviews ( Berry et al, 2019 ; Muller and Kogan, 2010 ; Ryu et al, 2023 ) Observations ( Berry et al, 2017 ; Millen, 2000 ) Crowdsourcing ( Kornfield et al, 2022b ) Workflow design sessions ( Knapp et al, 2022 ; Lattie et al, 2021 ) Persona development ( Faily and Flechais, 2011 ; LeRouge et al, 2013 ) Resource and environment evaluation Interviews and/or surveys with service organizations Prototyping the product or service ( ideate , prototype , evaluate , and refine & develop ) What is the ideal format of, or platform for, the DMHI? What kinds of use pathways exist when using the DMHI?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… What are the determinants that may affect implementation of the DMHI and strategies that address those determinants? Community Engagement/Relationship Building ( Hayes, 2014 ; Le Dantec and Fox, 2015 ; Stiles-Shields et al, 2022 ) Volunteering Community meetings ( Harrington et al, 2019 ; Lu et al, 2023 ) Needs Elicitation Focus Groups ( Knapp et al, 2021 ; Kruzan et al, 2022a ; Lattie et al, 2020b ; Makosky Daley et al, 2010 ; Powell et al, 1996 ) Co-Design Workshops Interviews ( Berry et al, 2019 ; Muller and Kogan, 2010 ; Ryu et al, 2023 ) Observations ( Berry et al, 2017 ; Millen, 2000 ) Crowdsourcing ( Kornfield et al, 2022b ) Workflow design sessions ( Knapp et al, 2022 ; Lattie et al, 2021 ) Persona development ( Faily and Flechais, 2011 ; LeRouge et al, 2013 ) Resource and environment evaluation Interviews and/or surveys with service organizations Prototyping the product or service ( ideate , prototype , evaluate , and refine & develop ) What is the ideal format of, or platform for, the DMHI? What kinds of use pathways exist when using the DMHI?…”
Section: Discussionmentioning
confidence: 99%
“…Needs Elicitation Focus Groups ( Knapp et al, 2021 ; Kruzan et al, 2022a ; Lattie et al, 2020b ; Makosky Daley et al, 2010 ; Powell et al, 1996 ) Co-Design Workshops Interviews ( Berry et al, 2019 ; Muller and Kogan, 2010 ; Ryu et al, 2023 ) Observations ( Berry et al, 2017 ; Millen, 2000 ) Crowdsourcing ( Kornfield et al, 2022b ) Workflow design sessions ( Knapp et al, 2022 ; Lattie et al, 2021 ) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the evidence synthesis found more of a focus on adults, there was a slightly higher number of targeted strategies for young people. However, there is a need for more effective qualitative strategies such as in designing and implementing youth-oriented tailored solutions [68] and implementing a centralized DMH platform to improve stakeholder accessibility [74]. The previous review of Spadaro et al [51] suggested overhauling the application of codesign, behavior theories, and clinical evaluation.…”
Section: Secondary Findings Of Empirical Literaturementioning
confidence: 99%
“…Then, it may be possible to translate findings and reevaluate (cost-)effective ways of targeting young people in mental health care and suicide prevention. It is already apparent from the preliminary evidence on serving young people that there are issues with DMH platform accessibility [74] and DMHI implementation [75]. Furthermore, there are issues in the need for parental consent/involvement, as well as higher uptake and engagement through frequent screening especially in adolescents [65].…”
Section: Future Research Implications and Prospectsmentioning
confidence: 99%